Addressing the diagnostic and therapeutic dilemmas of ovarian immature teratoma: Report from a clinicopathologic consensus conference. (September 2022) - Pashankar, Farzana; Hanley, Krisztina; Lockley, Michelle; Stoneham, Sara; Nucci, Marisa R.; Reyes -Múgica, Miguel; Elishaev, Esther; Vang, Russell; Veneris, Jennifer; Rytting, Heather; Olson, Thomas; Hazard, Kim; et al.
Abstract: Ovarian immature teratoma is a rare subtype of germ cell tumour that can be pure or associated with non-teratomatous germ cell tumour elements and is graded based on extent of the immature neuroectodermal component. Immature teratoma (IT) can also be associated with somatic differentiation in the form of sarcoma, carcinoma, or extensive immature neuroectodermal elements and may produce low levels of serum alpha-fetoprotein. Variable interpretation of these issues underlies diagnostic and management dilemmas, resulting in substantial practice differences between paediatric and adult women with IT. The Malignant Germ Cell International Consortium (MaGIC) convened oncologists, surgeons, and pathologists to address the following crucial clinicopathologic issues related to IT: (1) grading of IT, (2) definition and significance of 'microscopic' yolk sac tumour, (3) transformation to a somatic malignancy, and (4) interpretation of serum tumour biomarkers. This review highlights the discussion, conclusions, and suggested next steps from this clinicopathologic conference. Highlights: Diagnosis and grading (three- vs. two-tier) of immature teratoma (IT) remains challenging. IT grade significantly affects treatment options. Treatment options for IT differ between children and adults. IT was discussed at a MaGIC-sponsored multidisciplinary conference. This review presents conference discussion, conclusions, and proposed next steps.